Hydrogen Passivation of M–N–C (M = Fe, Co) Catalysts for Storage Stability and ORR Activity Improvements (Adv. Mater. 38/2021). Issue 38 (21st September 2021) - Liu, Jieyuan; Wan, Xin; Liu, Shiyuan; Liu, Xiaofang; Zheng, Lirong; Yu, Ronghai; Shui, Jianglan
Abstract : Single‐Atom Catalysts Carbon‐supported single‐atom catalysts are subjected to surface oxidation and hydroxylation upon long‐term exposure to ambient environment, causing severe performance degradation. The hydrogen passivation strategy developed by Jianglan Shui and co‐workers in article number 2103600 can protect the catalytic active sites and ultimately improve the storage stability of single‐atom catalysts.